On Price Stability and Welfare - Yehoue, Etienne (IMF Working Papers; Working Paper ;, 2012)
The financial crisis in the advanced countries that began in 2007 has led central bankers to adopt unconventional policy measures as policy interest rates neared the zero bound. One suggestion (Blanchard, Dell'Ariccia, and Mauro, 2010) has been to raise inflation targets to provide more room for policy rate easing during crises. This paper addresses a different issue: the relationship between inflation and welfare. The literature is surveyed and a model is developed. A key conclusion is that an increase in inflation targets gives rise to additional welfare costs, even after the extra room to maneuver above the zero lower bound for nominal policy rates is taken into account. Based on parameter values that fit U.S. data, the additional welfare costs of raising inflation targets from 2 to 4 percent are estimated at about 0.3 percent of annual real income. A rise to 10 percent would yield additional welfare costs of about 1 percent of real income. Other parameter values yield welfare costs as high as 7 (respectively 30) percent of real income for raising inflation targets from 2 to 4 (respectively from 2 to 10) percent. The full costs of raising inflation targets are likely to be higher because the model used to generate these estimates does not account for higher inflation-induced volatility.